Early Warning For Earthquakes. - Enriquez, Alberto
This paper presents NASA scientist Friedemann Freund's experiments on why radio frequency phenomena precede some earthquakes. He demonstrated in the laboratory how the earth's crust can act as a gigantic battery to drive a geological radio circuit that extends more than 30 kilometers below the ground. It is too soon to say whether Freund's theories will be upheld or refuted, but the balance of expert opinion and evidence clearly is beginning to shift in his favor
Keywords: San Andreas Fault; Earthquake prediction; Electromagnetic precursors; Geological radio circuit; Hole currents; Igneous rocks; Oxygen bonds; Radio frequency phenomena